Carrying Capacity Assessment for Coastal Tourism and its Implication for Geographical Education - Ahyuni, Ahyuni; Nur, Hamdi (Sumatra Journal of Disaster, Geography and Geography Education, 2017)
Carrying capacity of coastal tourism need to be reviewed from the multiple aspect of ecology, physical, political and economic as well as socio-cultural. Then various indicators need to be formulated to make an assessment of the impact of coastal tourism development. The cases of coastal tourism could be an interesting topic to integrate the subject matter of geography. In this paper the framework of that carrying capacity is applied to Mandeh coastal tourism development in West Sumatra.